2021
DOI: 10.29407/js_unpgri.v7i3.16859
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of active recovery (jogging and cycling) post-football match simulation on athletes' heart rate and fatigue levels

Abstract: Active recovery is recommended to help the soccer player recover quickly. However, there has been no study comparing the most effective active recovery methods post-match. The purpose of this study was to compare active recovery (jogging and cycling) to the heart rate and fatigue level of athletes. This study uses an experimental method with a pretest-posttest crossover design approach. Subjects were 22 male amateur football athletes with an average (age, 19.40 ± 1.18 years; height, 170.04 ± 3.54 cm; weight, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Soccer, as a sport that requires high basic technical skills, such as passing, control, and dribbling, is integral to team success and individual performance (Akbar et al, 2021). Soccer, as a very popular global sport, requires players to have high basic technical skills, such as passing, control, and dribbling, as key elements in winning matches and achieving success (Corrigan et al, 2023;McCaskie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Soccer, as a sport that requires high basic technical skills, such as passing, control, and dribbling, is integral to team success and individual performance (Akbar et al, 2021). Soccer, as a very popular global sport, requires players to have high basic technical skills, such as passing, control, and dribbling, as key elements in winning matches and achieving success (Corrigan et al, 2023;McCaskie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high physical performance, soccer players face a busy match schedule, where players must repeatedly practice in a short time (Akbar, Marhaendro, Agus, Hita, & Ariestika, 2021). The amount of training that is carried out intensively will expend excessive energy, causing fatigue in soccer players during matches.…”
Section: Introductionmentioning
confidence: 99%
“…Plyometrics is an exercise that involves and utilizes the muscle stretch reflex mechanism to increase the efficiency of force production in a joint (muscles,Jurnal SPORTIF: Jurnal Penelitian Pembelajaran,8 (4) 328 bones, and joints) or improve physical work performance (Akbar et al, 2021). Sammoud et al, (2021) explained that the main purpose of plyometric training is to train muscles to produce strength and speed by utilizing shortening and stretching cycles (SSC), when a combination of muscles and tendons is stretched rapidly, as is the case in fast eccentric movements, the nervous system responds by recruiting most of the muscle fibers to produce more power in an attempt to reverse the direction of movement (Derek Hansen, 2017) Previous literature studies revealed that martial arts often perform high-intensity plyometric training models to achieve success when competing, as described above or before this paragraph.…”
Section: Introductionmentioning
confidence: 99%